Problems and prospects of the hotel business development in Kharkiv region within international integration - Kuchechuk, Larisa; Chernyusch, Kateryna (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2018)
The authors analyze the current condition of the hotel economy development in Ukraine in general and in the Kharkiv region in particular, identify the main problems, which hinder its effective development and interfere with using of the advantages of international integration, suggest ways of solving these problems. Having analyzed, systematized and generalized the scientific works by many scientists, the authors consider and form a new concept of «hotel» and «hotel industry», which better reflects its essence. The authors analyze the most common and precise approaches to the classification of accommodation facilities and provide a standard classification of accommodation facilities for tourists, which are now widely used in Ukraine and in many countries around the world. The article offers the rating of the best hotels in Kharkiv region according to travelers’ estimation, which was created via the data of the largest traveler community in the world «TripAdvisor», analyzes features of their activities and reveals that hotels of category **** are popular and in demand by tourists